Purchase order for supply of electrical cables for HVAC work for BRACU new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This purchase order has been made between Poly Cables Ind. Limited for supply of electrical cables for HVAC work for BRACU new campus building project.